2015
DOI: 10.1039/c4ta06128d
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the humidity stability of organic–inorganic perovskite solar cells using ultrathin Al2O3layers prepared by atomic layer deposition

Abstract: The high polarity of water molecules inevitably causes the decomposition of perovskites. We retard the degradation by introducing an ultrathin ALD–Al2O3layer, which has almost no negative effect on performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
258
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 324 publications
(269 citation statements)
references
References 30 publications
7
258
3
1
Order By: Relevance
“…It has been found that adding an ultrathin compact Al 2 O 3 layer on top of the hole transport layer effectively blocks the water without significantly reducing the overall device efficiency, thus improving the overall stability of the system. [69] The perovskite layer also has a tendency to affect the metal contact layers by reaction of mobile I − ions from the perovskite with the metal contacts, leading to drastic changes in the relative energy levels, and thus in the overall solar cell performance. The reaction of iodide with metal electrodes, such as silver, caused an irreversible degradation of the metal contact on the microscale, and thus a failure of the solar cell.…”
Section: Perovskite Solar Cell Heterojunction Interface Characterizationmentioning
confidence: 99%
“…It has been found that adding an ultrathin compact Al 2 O 3 layer on top of the hole transport layer effectively blocks the water without significantly reducing the overall device efficiency, thus improving the overall stability of the system. [69] The perovskite layer also has a tendency to affect the metal contact layers by reaction of mobile I − ions from the perovskite with the metal contacts, leading to drastic changes in the relative energy levels, and thus in the overall solar cell performance. The reaction of iodide with metal electrodes, such as silver, caused an irreversible degradation of the metal contact on the microscale, and thus a failure of the solar cell.…”
Section: Perovskite Solar Cell Heterojunction Interface Characterizationmentioning
confidence: 99%
“…After exposing to air for 18 h with a relative humidity of 60% at 35 °C , the Al2O3 modified device maintained 48% of its original efficiency, whereas the device without modification kept only 20% of the original efficiency. Very recently, an ultrathin Al2O3 buffer layer was deposited onto the top of spiro-MeOTAD layer by atomic layer deposition (ALD) [17]. The thickness of Al2O3 layer was precisely controlled by controlling the ALD cycles.…”
Section: +mentioning
confidence: 99%
“…[9] Beside environmental factors such as thermal stress and UV-light irradiation in air, [9][10][11] humidity-induced changes to the perovskite structure have been identified as one of the major degradation pathways which strongly affects device lifetime. [12,13] Degradation upon exposure to moisture has so far only been suppressed by physical encapsulation or through the introduction of organic or inorganic passivation layers [14][15][16] which may place constraints on device performance. Fully understanding the effect of water on perovskite processing and degradation is thus important to formulate new solutions to this challenge.…”
Section: Introductionmentioning
confidence: 99%